2019
DOI: 10.1002/adma.201904598
|View full text |Cite
|
Sign up to set email alerts
|

Remote Magnetic Nanoparticle Manipulation Enables the Dynamic Patterning of Cardiac Tissues

Abstract: regenerative medicine and remains a major challenge. A multitude of technologies have been described to control the spatial organization of cells in 3D engineered heart constructs including mechanical strain/load [1] and chronic electrical stimulation. [2] Other approaches to guide cellular organization have been reported using microfluidic platforms, [3] light-triggered activation of biomolecules, [4] and 3D bioprinting. [5] However, these techniques often involve elaborate, macroscale stimulation systems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 37 publications
0
75
0
Order By: Relevance
“…Furthermore, the presence of magnetic Fe segments in the nanobarcodes can allow magnetic control of ligand alignment and in situ motion to remotely regulate numerous host cells. [ 16,38,39 ] These findings can be applied to design novel biomaterials presenting heterogeneous nano‐ligand sequences at terminal sides and/or low nano‐ligand sequences to stimulate the adhesion of host cells.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the presence of magnetic Fe segments in the nanobarcodes can allow magnetic control of ligand alignment and in situ motion to remotely regulate numerous host cells. [ 16,38,39 ] These findings can be applied to design novel biomaterials presenting heterogeneous nano‐ligand sequences at terminal sides and/or low nano‐ligand sequences to stimulate the adhesion of host cells.…”
Section: Methodsmentioning
confidence: 99%
“…There are a number of methodologies developed for fabrication of complex 3D cell systems in vitro. [ 3–7,13,14 ] Directed assembly allows manual positioning or stacking building blocks to form 3D architectures. [ 15,16 ] Birey et al.…”
Section: Figurementioning
confidence: 99%
“…In one such study, magnetic ferumoxytol nanoparticles were used to label cardiosphere-derived stem cells and to target them into coronary arteries of rat post-myocardial infarction ischemia/reperfusion models, thereby addressing the ordinarily low level of stem cell retention and engraftment [100]. In another study, magnetic iron oxide nanoparticles have also been utilized in guiding tissue scaffold structure following implantation into a rat model [101]. In this study, Zwi-Dantsis et al demonstrated that magnetic iron oxide nanoparticles conjugated to antibodies directed at signal-regulatory protein alpha (SIRPA) could be utilized to manipulate human cardiomyocytes in situ with magnets.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%